Automação residencial utilizando Raspberry Pi para auxílio a pessoas com deficiência motora - Passini, Bruno Paiva (Universidade Federal de São Carlos, 2022)
This work presents a system that was developed to allow people with motor difficulties to remotely control the operation of devices that act on the well-being of the environment. Commands are entered into the system via a cellphone that communicates with a single- board computer, the Raspberry Pi, which receives user commands to turn it on or off. A temperature and humidity sensor are used to control the operating range of a heater and humidifier when turned on.
Home automation using Raspberry Pi for helping persons with mobility impairment
Keywords: Dificuldades motoras; Bem-estar ambiente; Telefone celular; Mobility impairment; Health care environment; Raspberry Pi; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES